Síntese enzimática de ésteres catalisada por lipases imobilizadas em diferentes suportes - Lima, Lionete Nunes de (Universidade Federal de São Carlos, 2013)
Lipases are enzymes of great biotechnological relevance. Besides its natural function (hydrolysis of triglycerides), they are capable of catalyzing regio- and enantioselective hydrolysis and synthesis of numerous esters. Pseudomonas fluorescens lipase (LPF) was immobilized on different supports and with different methods and was applied on the synthesis of compounds of industrial interest. The efficiency of these syntheses with the biocatalyst PFL-octyl-silica, PFL-XAD 7 HP and PFL-polystyrene were used on the production of ethylic biodiesel from babassu oil. The best yield (100% within 24 h) was obtained with PFL immobilized on octyl-silica (PFL-octyl-silica). This derivative and commercial immobilized lipases (Candida antarctica lipase, CALB IM; Thermomyces lanuginosus lipase, LTL IM) were used on the production of ethylic biodiesel from soybean oil, showing similar yields within 48 h of reaction time (80%). On the synthesis of aromas, the biocatalysts PFL-octyl-silica, CALB IM, LTL IM and LPF IM (commercial immobilized Pseudomonas fluorescens lipase) presented similar performance (yield above 90% within 24 h of reaction time). Yields of about 95% were obtained within 12 h of reaction time with the biocatalysts PFL-octyl-silica and CALB IM, being able to be reused in eight successive batches. CALB IM produced fructose oleate (55 ºC, 24 h, oleic acid:fructose molar ratio 1:2) with 96% yield, whereas the derivative PFL-octyl.-silica yielded 57% (45 ºC, 72 h, molar ratio 1:1). PFL immobilized on octyl-agarose and octadecyl-Sepabeads presented an immobilization yield of 99%, rendering hyperactivated derivatives (150% and 300% of recovered activity, respectively). The monomeric form of the enzyme could be immobilized on glyoxyl-agarose at 25 ºC, pH 10.5 (100 mM sodium bicarbonate buffer), however, in the presence of a surfactant (Triton X-100 0,5% v/v). On the hydrolysis of (R,S)-ethyl-2-hydroxy-4-phenylbutyrate, PFL immobilized on octylagarose (open conformation) and on glyoxyl-agarose (in the form of bimolecular ...